Ibandronate treatment of diffuse sclerosing osteomyelitis of the mandible: Pain relief and insight into pathogenesis. Issue 9 (November 2015) - Otto, Sven; Troeltzsch, Matthias; Burian, Egon; Mahaini, Salah; Probst, Florian; Pautke, Christoph; Ehrenfeld, Michael; Smolka, Wenko
Abstract: Purpose: Diffuse sclerosing osteomyelitis of the mandible (DSO) is a rare and poorly understood disease. Current treatment protocols, including steroid or analgesic medication and corticotomies, show poor or frustrating outcome results and are accompanied by potentially severe side effects. The aim of this study was to determine whether there is a beneficial role of infusions with nitrogen-containing bisphosphonates (ibandronate) in acute conditions of DSO. Material and methods: Eleven patients were enrolled in the study. In acute conditions of treatment-resistant DSO, single-shot infusions of ibandronate (6 mg) were administered. Pain levels were documented 10 days before and after the infusion on a visual analogue scale (VAS). Patients were monitored regularly. Results: Of the 11 patients, 10 showed a distinct improvement in pain (based on VAS scores) within 48–72 h after infusion. The pain levels of the patients were significantly lower after ibandronate infusions (p < 0.01). The majority of patients were free or almost free of complaints over the following months. Four of the 11 patients returned for repeated infusions. At the time of writing, no severe side effects have been observed, and in particular there has been no case of medication-related jaw osteonecrosis. Conclusion: We conclude that single-shot bisphosphonate infusions on demand are promising treatment alternatives in acute DSO. Single-shot bisphosphonate infusions of ibandronate were well tolerated and resulted in distinct, long lasting improvement in subjective pain levels based on VAS scores.